Analyzing the effects of economic development on the transition to cleaner production of China's energy system under uncertainty. (10th January 2021) - Suo, C.; Li, Y.P.; Nie, S.; Lv, J.; Mei, H.; Ma, Y.
Abstract: A number of conflicting issues such as growing economic demand, increasing energy supply, shrinking energy resources, changing climate condition, as well as tightening environmental requirement pose great challenges to decision makers for planning energy system towards cleaner production and sustainable development. In this study, an ensemble energy system model for China (named as CN-EES model) is developed through incorporating computable general equilibrium model and interval-parameter programming method within an energy system optimization framework. The CN-EES model is capable of predicting energy demands under different economic-development scenarios, reflecting uncertainties derived from long-term (2021–2050) planning period, and providing optimal solutions for China's energy system transition and management. Results under multiple scenarios have been generated and are used for disclosing the impacts of economic development on the transition to cleaner production of China's energy system. Our main findings are (a) fossil fuel (i.e., coal, oil and gas): would keep the leading position for China's energy system, but its share in the total energy supply would decline to 61.09% by 2050; (b) China's energy-supply security would be challenged because the fossil fuel import would be surpassed the international warning line in 2041–2045, even the speed of the economic development is slowed down; (c) renewable energy would replace fossil fuel to dominate the national electric power system after 2041; (d) China's energy system would transfer towards a clean and low-carbon "modern energy system"; however, there is still enormous pressure on carbon dioxide and air pollutant emissions under high-speed economic development scenarios. The findings can help decision makers to well understand the effects of economic development on China's energy system transition and effectively cope with issues of energy supply, environmental protection, and climate change. Graphical abstract: Image 1 Highlights: An ensemble energy system model for China is developed. China's energy system would be dominated by fossil fuel in 2021–2050. Renewable energy would take the largest share in electricity generation after 2041. Energy-supply security would be challenged even at a low-speed economic development. China's energy system would transfer towards a clean and low-carbon one.